A method for preparing starch-modified surfactant for basalt fiber

Through the preparation method of starch modified surfactant, the problem of poor interfacial wetting in basalt composite materials is solved, which significantly improves the mechanical properties of the composite plate and extends its application scenarios.

CN116355108BActive Publication Date: 2025-04-15BEIJING XUANZE NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310278291.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-21
Publication Date
2025-04-15
Estimated Expiration
2043-03-21

AI Technical Summary

Technical Problem

In basalt composite materials, the interface wettability between resin and basalt fibers is poor, resulting in poor mechanical properties of the composite materials and micropores and cracks, limiting their application scenarios.

Method used

The preparation method of starch-modified surfactant is adopted to enhance its binding force with basalt fibers by combining oxidized modified starch and grafted etherified silane-modified starch, and improve the interface effect between the resin and the fibers.

Benefits of technology

It significantly improves the parallel layer shear strength of the basalt fiber composite panel, improves the mechanical properties of the material, enhances the combination of fibers and resins, and extends its application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a method for preparing a starch-modified surfactant for basalt fiber, comprising the following steps: adding distilled water to soluble starch to prepare a 15% to 30% starch solution, adjusting the pH value to 10 to 11 with 5% sodium hydroxide, heating in a water bath at 30 to 45°C, adding an oxidant of 3% to 20% of the mass of the starch, oxidizing at a constant temperature for 3 to 4 hours, neutralizing with a hydrochloric acid solution, adding a reducing agent of 2 to 20% of the oxidant dosage of ascorbic acid and sodium bisulfite, terminating the reaction, filtering, washing, and drying to obtain oxidized modified starch. The invention enhances the binding of the impregnating agent to the fiber, and the modified starch itself has abundant functional groups, many of which can participate in the curing process of the resin, enhancing the binding of the impregnating agent to the resin through chemical reactions, and improving the interfacial bonding strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surfactants, and in particular to a method for preparing a starch-modified surfactant for basalt fiber. Background Art

[0002] Basalt fiber is made of natural basalt as the main raw material, which is formed by drawing after high-temperature melting. It is an inorganic environmentally friendly, green and high-performance fiber material. Basalt composite materials have been widely used in the fields of construction, transportation, petrochemicals, etc., and have achieved good results. Composite materials are materials composed of two or more substances. They can give full play to the advantages of various materials, overcome the defects of single materials, and expand the application range of materials. Due to the characteristics of light weight, high strength, easy processing and molding, excellent elasticity, chemical corrosion resistance and good weather resistance, composite materials have gradually replaced wood and metal alloys and are widely used in aerospace, automobiles, electronics and electrical, construction and other fields. In recent years, it has developed rapidly.

[0003] The mechanical properties of fiber composites mainly depend on the properties of the matrix material, the properties of the reinforcement, and the properties of the interface between the matrix and the reinforcement. Basalt composites are mainly composed of two components: basalt reinforced fibers and resins. In order for composites to obtain excellent performance, the resin and basalt fibers must have good wettability. If the surface properties of the two materials are very different, the interface wetting effect will be poor, and the resin will not be able to tightly bond with the basalt fibers. There will be undesirable problems such as micropores and cracks at the interface between the two. When the composite material is in a certain stress environment, fracture and delamination are prone to occur at the material interface, resulting in poor mechanical properties of the composite material, limiting its development of a wider range of application scenarios.

[0004] Based on this, the present invention provides a method for preparing a starch-modified surfactant for basalt fiber. Summary of the invention

[0005] In view of the defects of the prior art, the purpose of the present invention is to provide a method for preparing a starch-modified surfactant for basalt fiber to solve the problems raised in the above background technology.

[0006] The present invention solves the technical problem by adopting the following technical solution:

[0007] The present invention provides a method for preparing a starch-modified surfactant for basalt fiber, comprising the following steps:

[0008] Soluble starch is added with distilled water to prepare a 15% to 30% starch solution, the pH value is adjusted to 10 to 11 with 5% sodium hydroxide, heated in a water bath at 30 to 45°C, an oxidant is added at 3% to 20% of the mass of the starch, oxidized at a constant temperature for 3 to 4 hours, neutralized with a hydrochloric acid solution, a reducing agent ascorbic acid and sodium bisulfite at 2 to 20% of the amount of the oxidant are added, the reaction is terminated, filtered, washed, and dried to obtain oxidized modified starch;

[0009] The modified starch was prepared into a suspension with a starch mass fraction of 40% to 60% using anhydrous ethanol as solvent, the pH value was adjusted to 8.5 to 10 with sodium hydroxide, 2% to 4% of 3-glycidyloxypropylmethyldiethoxysilane based on the dry weight of starch was added, the mixture was sealed and nitrogen was passed through, and the reaction was carried out at a constant temperature of 50 to 60°C for 10 to 20 h. The product was neutralized with hydrochloric acid to a pH value of 6.5 to 7.5, and dried with air at 80°C for 4 h to obtain the grafted etherified silane-modified starch.

[0010] Preferably, the oxidant is one of sodium hypochlorite, hydrogen peroxide and ammonium persulfate.

[0011] Preferably, the grafted etherified silane-modified starch product is further added with a total amount of 1-5% of a modification additive.

[0012] Preferably, the preparation method of the modified additive is:

[0013] The carbon nanotubes are placed in a 2-3 times hydrochloric acid solution and stirred evenly, then 1-3% of lanthanum sulfate and 1-5% of hydroxyl modifier are added to the total amount of carbon nanotubes, stirred evenly, and finally washed with water and dried, and then stirred and dispersed fully in a 3-5 times silane coupling agent solution, and finally washed with water and dried to obtain a modified additive.

[0014] Preferably, the mass fraction of the hydrochloric acid solution is 5-10%.

[0015] Preferably, the preparation method of the hydroxyl modifier is:

[0016] Hydroxyapatite is added to the sodium alginate solution at a weight ratio of 1:5, and then 2-5% of sodium oxalate and 1-5% of silica sol are added to the total amount of hydroxyapatite, and the mixture is stirred sufficiently to obtain a hydroxyl modifier.

[0017] Preferably, the mass fraction of the sodium alginate solution is 20-30%.

[0018] Preferably, the silane coupling agent solution is 2-3 parts of silane coupling agent, 10-20 parts of deionized water, and 2-4 parts of phosphate buffer solution.

[0019] Preferably, the silane coupling agent is coupling agent KH560.

[0020] Preferably, the pH value of the phosphate buffer solution is 5.5.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The surfactant molecules designed by the present invention have the characteristics of high molecular weight and rich functional groups, and can achieve perfect combination of two materials through physical and chemical action: the modified starch has a complex molecular structure and can be well coated on the surface of basalt fiber, and the silane group of the coupling agent reacts chemically with the fiber surface to further enhance the combination of the sizing agent and the fiber. The modified starch itself has rich functional groups, many of which can participate in the curing process of the resin, and enhance the combination of the sizing agent and the resin through chemical reactions. Implementation

[0023] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] A method for preparing a starch-modified surfactant for basalt fiber in this embodiment comprises the following steps:

[0025] Soluble starch is added with distilled water to prepare a 15% to 30% starch solution, the pH value is adjusted to 10 to 11 with 5% sodium hydroxide, heated in a water bath at 30 to 45°C, an oxidant is added at 3% to 20% of the mass of the starch, oxidized at a constant temperature for 3 to 4 hours, neutralized with a hydrochloric acid solution, a reducing agent ascorbic acid and sodium bisulfite at 2 to 20% of the amount of the oxidant are added, the reaction is terminated, filtered, washed, and dried to obtain oxidized modified starch;

[0026] The modified starch was prepared into a suspension with a starch mass fraction of 40% to 60% using anhydrous ethanol as solvent, the pH value was adjusted to 8.5 to 10 with sodium hydroxide, 2% to 4% of 3-glycidyloxypropylmethyldiethoxysilane based on the dry weight of starch was added, the mixture was sealed and nitrogen was passed through, and the reaction was carried out at a constant temperature of 50 to 60°C for 10 to 20 h. The product was neutralized with hydrochloric acid to a pH value of 6.5 to 7.5, and dried with air at 80°C for 4 h to obtain the grafted etherified silane-modified starch.

[0027] The oxidant in this embodiment is sodium hypochlorite.

[0028] The grafted etherified silane-modified starch product of this example is further added with a total amount of 1-5% of a modification additive.

[0029] The preparation method of the modified additive of this embodiment is:

[0030] The carbon nanotubes are placed in a 2-3 times hydrochloric acid solution and stirred evenly, then 1-3% of lanthanum sulfate and 1-5% of hydroxyl modifier are added to the total amount of carbon nanotubes, stirred evenly, and finally washed with water and dried, and then stirred and dispersed fully in a 3-5 times silane coupling agent solution, and finally washed with water and dried to obtain a modified additive.

[0031] The mass fraction of the hydrochloric acid solution in this embodiment is 5-10%.

[0032] The preparation method of the hydroxy modifier of this embodiment is:

[0033] Hydroxyapatite is added to the sodium alginate solution at a weight ratio of 1:5, and then 2-5% of sodium oxalate and 1-5% of silica sol are added to the total amount of hydroxyapatite, and the mixture is stirred sufficiently to obtain a hydroxyl modifier.

[0034] The mass fraction of the sodium alginate solution in this embodiment is 20-30%.

[0035] The silane coupling agent solution of this embodiment is 2-3 parts of silane coupling agent, 10-20 parts of deionized water, and 2-4 parts of phosphate buffer solution.

[0036] The silane coupling agent in this embodiment is coupling agent KH560.

[0037] The pH value of the phosphate buffer solution in this example is 5.5.

[0038] The parallel layer shear strength test of the Xuan fiber composite board is carried out according to the provisions of the standard "Thermosetting resin industrial hard laminate for electrical appliances Part 2: Test method" GB / T 1303.2-2009. The rectangular specimen dimensions are as follows: length: 20 mm ± 0.1mm; width and thickness: 5 mm (tolerance is -0.15~0mm). The width of each group of specimens (the dimension along the layer and perpendicular to the length direction of the specimen) should be as similar as possible, and the difference should not exceed 0.01 mm.

[0039] The test specimens were made according to the standard requirements, including two types of Xuanxian fiber cloth with starch surfactant coated on the surface and one without spraying. The resins were polyester resin and epoxy resin, and the starch surface surfactant was tested to see whether it played a role in the combination of different resins and Xuanxian. The test results show that starch-modified surfactant can increase the parallel layer shear strength of Xuanxian composite board by 15-20%. In the process of combining Xuanxian and resin, the interface effect of the two materials is improved through physical and chemical effects, so that the mechanical properties of the composite board are improved. In addition, the surfactant is suitable for both polyester resin and epoxy resin.

[0040] Examples:

[0041]

[0042] Performance test results:

[0043]

[0044] Optimization example 1.

[0045] A method for preparing a starch-modified surfactant for basalt fiber in this embodiment comprises the following steps:

[0046] Soluble starch is added with distilled water to prepare a 15% starch solution, the pH value is adjusted to 10 with 5% sodium hydroxide, heated in a water bath at 30°C, an oxidant is added at 3% of the mass of the starch, oxidized at a constant temperature for 3 hours, neutralized with a hydrochloric acid solution, a reducing agent ascorbic acid and sodium bisulfite at 2% of the oxidant amount are added, the reaction is terminated, filtered, washed, and dried to obtain oxidized modified starch;

[0047] The modified starch was prepared into a suspension with a starch mass fraction of 40% using anhydrous ethanol as solvent, the pH value was adjusted to 8.5 with sodium hydroxide, and 2% of 3-glycidyloxypropylmethyldiethoxysilane was added based on the dry weight of starch. The mixture was sealed and protected with nitrogen, and the reaction was carried out at a constant temperature of 50°C for 10 h. The product was neutralized with hydrochloric acid to a pH value of 6.5, and then dried with air at 80°C for 4 h to obtain the grafted etherified silane-modified starch.

[0048] The oxidants in this embodiment are sodium hypochlorite, hydrogen peroxide, and ammonium persulfate.

[0049] In this example, a total amount of 1% of a modification additive is added to the grafted etherified silane-modified starch product.

[0050] The preparation method of the modified additive of this embodiment is:

[0051] The carbon nanotubes were placed in a 2-fold hydrochloric acid solution and stirred evenly, and then 1% of lanthanum sulfate and 1% of a hydroxyl modifier were added to the total amount of the carbon nanotubes and stirred evenly, and finally washed with water and dried, and then stirred and dispersed sufficiently in a 3-fold silane coupling agent solution, and finally washed with water and dried to obtain a modified additive.

[0052] The mass fraction of the hydrochloric acid solution in this embodiment is 5%.

[0053] The preparation method of the hydroxy modifier of this embodiment is:

[0054] Hydroxyapatite was added to the sodium alginate solution at a weight ratio of 1:5, and then 2% of sodium oxalate and 1% of silica sol were added to the total amount of hydroxyapatite, and the mixture was stirred thoroughly to obtain a hydroxyl modifier.

[0055] The mass fraction of the sodium alginate solution in this embodiment is 20%.

[0056] The silane coupling agent solution of this embodiment is 2 parts of silane coupling agent, 10 parts of deionized water, and 2 parts of phosphate buffer solution.

[0057] The silane coupling agent in this embodiment is coupling agent KH560.

[0058] The pH value of the phosphate buffer solution in this example is 5.5.

[0059] Optimization example 2.

[0060] A method for preparing a starch-modified surfactant for basalt fiber in this embodiment comprises the following steps:

[0061] Soluble starch is added with distilled water to prepare a 30% starch solution, the pH value is adjusted to 11 with 5% sodium hydroxide, heated in a water bath at 45°C, an oxidant is added at 20% of the mass of the starch, oxidized at a constant temperature for 4 hours, neutralized with a hydrochloric acid solution, a reducing agent ascorbic acid and sodium bisulfite at 20% of the amount of the oxidant are added, the reaction is terminated, filtered, washed, and dried to obtain oxidized modified starch;

[0062] The modified starch was prepared into a suspension with a starch mass fraction of 60% using anhydrous ethanol as solvent, the pH value was adjusted to 10 with sodium hydroxide, 4% of 3-glycidyloxypropylmethyldiethoxysilane based on the dry weight of starch was added, the mixture was sealed and nitrogen was passed through, and the reaction was carried out at a constant temperature of 60°C for 20 h. The product was neutralized with hydrochloric acid to a pH value of 7.5, and dried with air at 80°C for 4 h to obtain the grafted etherified silane-modified starch.

[0063] The oxidant in this embodiment is ammonium persulfate.

[0064] In this example, a total amount of 5% of a modification additive is added to the grafted etherified silane-modified starch product.

[0065] The preparation method of the modified additive of this embodiment is:

[0066] The carbon nanotubes were placed in a 3-fold hydrochloric acid solution and stirred evenly, and then 3% of lanthanum sulfate and 5% of hydroxyl modifier were added to the total amount of carbon nanotubes, stirred evenly, and finally washed with water and dried. Then, they were stirred and dispersed sufficiently in a 5-fold silane coupling agent solution, and finally washed with water and dried to obtain a modified additive.

[0067] The mass fraction of the hydrochloric acid solution in this embodiment is 10%.

[0068] The preparation method of the hydroxy modifier of this embodiment is:

[0069] Hydroxyapatite was added to the sodium alginate solution at a weight ratio of 1:5, and then 5% of sodium oxalate and 5% of silica sol were added to the total amount of hydroxyapatite, and the mixture was stirred thoroughly to obtain a hydroxyl modifier.

[0070] The mass fraction of the sodium alginate solution in this embodiment is 30%.

[0071] The silane coupling agent solution of this embodiment is 3 parts of silane coupling agent, 20 parts of deionized water and 4 parts of phosphate buffer solution.

[0072] The silane coupling agent in this embodiment is coupling agent KH560.

[0073] The pH value of the phosphate buffer solution in this example is 5.5.

[0074] Optimization example 3.

[0075] A method for preparing a starch-modified surfactant for basalt fiber in this embodiment comprises the following steps:

[0076] Soluble starch is added with distilled water to prepare a 18% starch solution, the pH value is adjusted to 10 with 5% sodium hydroxide, heated in a water bath at 40°C, an oxidant is added at 10% of the mass of the starch, oxidized at a constant temperature for 3.2 hours, neutralized with a hydrochloric acid solution, and a reducing agent ascorbic acid and sodium bisulfite at 10% of the amount of the oxidant are added to terminate the reaction, filtered, washed, and dried to obtain oxidized modified starch;

[0077] The modified starch was prepared into a suspension with a starch mass fraction of 50% using anhydrous ethanol as solvent, the pH value was adjusted to 9.0 with sodium hydroxide, and 2% of 3-glycidyloxypropylmethyldiethoxysilane was added based on the dry weight of starch. The mixture was sealed and protected with nitrogen, and the reaction was carried out at a constant temperature of 55°C for 15 h. The product was neutralized with hydrochloric acid to a pH value of 7.0, and dried with air at 80°C for 4 h to obtain the grafted etherified silane-modified starch.

[0078] The oxidants in this embodiment are sodium hypochlorite, hydrogen peroxide, and ammonium persulfate.

[0079] The grafted etherified silane-modified starch product of this example is further added with a total amount of 1-5% of a modification additive.

[0080] The preparation method of the modified additive of this embodiment is:

[0081] The carbon nanotubes were placed in a 2.5 times hydrochloric acid solution and stirred evenly, and then 2% of lanthanum sulfate and 3% of hydroxyl modifier were added to the total amount of carbon nanotubes, stirred evenly, and finally washed with water and dried. Then, they were stirred and dispersed sufficiently in a 4 times silane coupling agent solution, and finally washed with water and dried to obtain a modified additive.

[0082] The mass fraction of the hydrochloric acid solution in this embodiment is 7%.

[0083] The preparation method of the hydroxy modifier of this embodiment is:

[0084] Hydroxyapatite was added to the sodium alginate solution at a weight ratio of 1:5, and then 3% of sodium oxalate and 2% of silica sol were added to the total amount of hydroxyapatite, and the mixture was stirred thoroughly to obtain a hydroxyl modifier.

[0085] The mass fraction of the sodium alginate solution in this embodiment is 25%.

[0086] The silane coupling agent solution of this embodiment is 2.5 parts of silane coupling agent, 15 parts of deionized water, and 3 parts of phosphate buffer solution.

[0087] The silane coupling agent in this embodiment is coupling agent KH560.

[0088] The pH value of the phosphate buffer solution in this example is 5.5.

[0089] Optimization example 4.

[0090] A method for preparing a starch-modified surfactant for basalt fiber in this embodiment comprises the following steps:

[0091] Soluble starch is added with distilled water to prepare a 17% starch solution, the pH value is adjusted to 10.21 with 5% sodium hydroxide, heated in a water bath at 36°C, an oxidant is added at 10% of the mass of the starch, oxidized at a constant temperature for 3.2 hours, neutralized with a hydrochloric acid solution, and a reducing agent ascorbic acid and sodium bisulfite at 10% of the amount of the oxidant are added to terminate the reaction, filtered, washed, and dried to obtain oxidized modified starch;

[0092] The modified starch was prepared into a suspension with a starch mass fraction of 50% using anhydrous ethanol as solvent, the pH value was adjusted to 8.9 with sodium hydroxide, 3% of 3-glycidyloxypropylmethyldiethoxysilane based on the dry weight of starch was added, the mixture was sealed and nitrogen was passed through, and the reaction was carried out at a constant temperature of 52°C for 12 hours. The product was neutralized with hydrochloric acid to a pH value of 6.7, and dried with air at 80°C for 4 hours to obtain the grafted etherified silane-modified starch.

[0093] The oxidant in this embodiment is ammonium persulfate.

[0094] In this example, a total amount of 2% of a modification additive is added to the grafted etherified silane-modified starch product.

[0095] The preparation method of the modified additive of this embodiment is:

[0096] The carbon nanotubes are placed in a 2-fold hydrochloric acid solution and stirred evenly, and then 2% of lanthanum sulfate and 2% of a hydroxyl modifier are added to the total amount of the carbon nanotubes, stirred evenly, and finally washed with water and dried. Then, the mixture is stirred and dispersed sufficiently in a 4-fold silane coupling agent solution, and finally washed with water and dried to obtain a modified additive.

[0097] The mass fraction of the hydrochloric acid solution in this embodiment is 6%.

[0098] The preparation method of the hydroxy modifier of this embodiment is:

[0099] Hydroxyapatite was added to the sodium alginate solution at a weight ratio of 1:5, and then 3% of sodium oxalate and 2% of silica sol were added to the total amount of hydroxyapatite, and the mixture was stirred thoroughly to obtain a hydroxyl modifier.

[0100] The mass fraction of the sodium alginate solution in this embodiment is 22%.

[0101] The silane coupling agent solution of this embodiment is 2 parts of silane coupling agent, 12 parts of deionized water, and 3 parts of phosphate buffer solution.

[0102] The silane coupling agent in this embodiment is coupling agent KH560.

[0103] The pH value of the phosphate buffer solution in this example is 5.5.

[0104] Optimization example 5.

[0105] A method for preparing a starch-modified surfactant for basalt fiber in this embodiment comprises the following steps:

[0106] Soluble starch is added with distilled water to prepare a 30% starch solution, the pH value is adjusted to 11 with 5% sodium hydroxide, heated in a water bath at 30-45°C, an oxidant is added in an amount of 18% of the mass of the starch, oxidized at a constant temperature for 4 hours, neutralized with a hydrochloric acid solution, a reducing agent ascorbic acid and sodium bisulfite in an amount of 20% of the oxidant, the reaction is terminated, filtered, washed, and dried to obtain oxidized modified starch;

[0107] The modified starch was prepared into a suspension with a starch mass fraction of 50% using anhydrous ethanol as solvent, the pH value was adjusted to 10 with sodium hydroxide, 4% of 3-glycidyloxypropylmethyldiethoxysilane based on the dry weight of starch was added, the mixture was sealed and nitrogen was passed through, and the reaction was carried out at a constant temperature of 55°C for 18 h. The product was neutralized with hydrochloric acid to a pH value of 7.2, and dried with air at 80°C for 4 h to obtain the grafted etherified silane-modified starch.

[0108] The oxidant in this embodiment is sodium hypochlorite.

[0109] In this example, a total amount of 4% of a modification additive is added to the grafted etherified silane-modified starch product.

[0110] The preparation method of the modified additive of this embodiment is:

[0111] The carbon nanotubes were placed in a 2.8 times hydrochloric acid solution and stirred evenly, and then 2% of lanthanum sulfate and 4% of hydroxyl modifier were added to the total amount of carbon nanotubes, stirred evenly, and finally washed with water and dried. Then, they were stirred and dispersed sufficiently in a 4 times silane coupling agent solution, and finally washed with water and dried to obtain a modified additive.

[0112] The mass fraction of the hydrochloric acid solution in this embodiment is 8%.

[0113] The preparation method of the hydroxy modifier of this embodiment is:

[0114] Hydroxyapatite was added to the sodium alginate solution at a weight ratio of 1:5, and then 4% of sodium oxalate and 4% of silica sol were added to the total amount of hydroxyapatite, and the mixture was stirred thoroughly to obtain a hydroxyl modifier.

[0115] The mass fraction of the sodium alginate solution in this embodiment is 28%.

[0116] The silane coupling agent solution of this embodiment is 3 parts of silane coupling agent, 18 parts of deionized water, and 4 parts of phosphate buffer solution.

[0117] The silane coupling agent in this embodiment is coupling agent KH560.

[0118] The pH value of the phosphate buffer solution in this example is 5.5.

[0119] Optimization Example 6.

[0120] A method for preparing a starch-modified surfactant for basalt fiber in this embodiment comprises the following steps:

[0121] Soluble starch is added with distilled water to prepare a 18% starch solution, the pH value is adjusted to 10 with 5% sodium hydroxide, heated in a water bath at 32°C, an oxidant is added at 4% of the mass of the starch, oxidized at a constant temperature for 3 hours, neutralized with a hydrochloric acid solution, a reducing agent ascorbic acid and sodium bisulfite at 3% of the oxidant amount are added, the reaction is terminated, filtered, washed, and dried to obtain oxidized modified starch;

[0122] The modified starch was prepared into a suspension with a starch mass fraction of 45% using anhydrous ethanol as solvent, the pH value was adjusted to 8.5 with sodium hydroxide, and 2% of 3-glycidyloxypropylmethyldiethoxysilane was added based on the dry weight of starch. The mixture was sealed and protected with nitrogen, and the reaction was carried out at a constant temperature of 50°C for 20 h. The product was neutralized with hydrochloric acid to a pH value of 6.5, and then dried with air at 80°C for 4 h to obtain the grafted etherified silane-modified starch.

[0123] The oxidant in this embodiment is ammonium persulfate.

[0124] In this example, a total amount of 5% of a modification additive is added to the grafted etherified silane-modified starch product.

[0125] The preparation method of the modified additive of this embodiment is:

[0126] The carbon nanotubes were placed in a 3-fold hydrochloric acid solution and stirred evenly, and then 3% of lanthanum sulfate and 5% of hydroxyl modifier were added to the total amount of carbon nanotubes, stirred evenly, and finally washed with water and dried. Then, they were stirred and dispersed sufficiently in a 5-fold silane coupling agent solution, and finally washed with water and dried to obtain a modified additive.

[0127] The mass fraction of the hydrochloric acid solution in this embodiment is 10%.

[0128] The preparation method of the hydroxy modifier of this embodiment is:

[0129] Hydroxyapatite was added to the sodium alginate solution at a weight ratio of 1:5, and then 4% of sodium oxalate and 5% of silica sol were added to the total amount of hydroxyapatite, and the mixture was stirred thoroughly to obtain a hydroxyl modifier.

[0130] The mass fraction of the sodium alginate solution in this embodiment is 28%.

[0131] The silane coupling agent solution of this embodiment is 3 parts of silane coupling agent, 20 parts of deionized water, and 4 parts of phosphate buffer solution.

[0132] The silane coupling agent in this embodiment is coupling agent KH560.

[0133] The pH value of the phosphate buffer solution in this example is 5.5.

[0134] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0135] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a starch-modified surfactant for basalt fiber, characterized in that: The following steps are involved: Soluble starch is added with distilled water to prepare a 15% to 30% starch solution, the pH value is adjusted to 10 to 11 with 5% sodium hydroxide, heated in a water bath at 30 to 45°C, an oxidant is added at 3% to 20% of the mass of the starch, oxidized at a constant temperature for 3 to 4 hours, neutralized with a hydrochloric acid solution, a reducing agent ascorbic acid and sodium bisulfite at 2 to 20% of the amount of the oxidant are added, the reaction is terminated, filtered, washed, and dried to obtain oxidized modified starch; Using anhydrous ethanol as solvent, the modified starch is prepared into a suspension with a starch mass fraction of 40% to 60%, the pH value is adjusted to 8.5 to 10 with sodium hydroxide, 2% to 4% of 3-glycidyloxypropylmethyldiethoxysilane based on the dry weight of starch is added, the mixture is sealed and nitrogen is passed through, and the reaction is carried out at a constant temperature of 50 to 60°C for 10 to 20 hours, the product is neutralized with hydrochloric acid to a pH value of 6.5 to 7.5, and air-dried at 80°C for 4 hours to obtain the grafted etherified silane-modified starch; The grafted etherified silane modified starch product is further added with a total amount of 1-5% of a modified additive to obtain the starch modified surfactant; the preparation method of the modified additive is: carbon nanotubes are added to a 2-3 times hydrochloric acid solution and stirred evenly, then 1-3% of lanthanum sulfate and 1-5% of a hydroxyl modifier are added to the total amount of the carbon nanotubes, stirred evenly, and finally washed with water and dried, and then stirred and dispersed fully in a 3-5 times silane coupling agent solution, and finally washed with water and dried to obtain the modified additive.

2. The method for preparing a starch-modified surfactant for basalt fiber according to claim 1, characterized in that: The oxidant is sodium hypochlorite, hydrogen peroxide, and ammonium persulfate.

3. The method for preparing a starch-modified surfactant for basalt fiber according to claim 1, characterized in that: The mass fraction of the hydrochloric acid solution is 5-10%.

4. The method for preparing a starch-modified surfactant for basalt fiber according to claim 1, characterized in that: The preparation method of the hydroxy modifier is: Hydroxyapatite is added to the sodium alginate solution at a weight ratio of 1:5, and then 2-5% of sodium oxalate and 1-5% of silica sol are added to the total amount of hydroxyapatite, and the mixture is stirred sufficiently to obtain a hydroxyl modifier.

5. The method for preparing a starch-modified surfactant for basalt fiber according to claim 4, characterized in that: The mass fraction of the sodium alginate solution is 20-30%.

6. The method for preparing a starch-modified surfactant for basalt fiber according to claim 5, characterized in that: The silane coupling agent solution comprises 2-3 parts of silane coupling agent, 10-20 parts of deionized water and 2-4 parts of phosphate buffer solution.

7. The method for preparing a starch-modified surfactant for basalt fiber according to claim 6, characterized in that: The silane coupling agent is coupling agent KH560.

8. The method for preparing a starch-modified surfactant for basalt fiber according to claim 7, characterized in that: The pH value of the phosphate buffer solution is 5.5.

Citation Information

Patent Citations

  • Preparation method of composite modified starch

    CN106967178A

  • Silane-modified oxidized starch adhesive as well as preparation method and application thereof

    CN107474759A

  • Preparation method of modified starch

    CN111363054A